Preparation of Al/AlN composites by in-situ reaction in the nitridation-induced self-forming process. (October 2022) - Kim, Jungjoon; Park, Jooyoung; Shim, Cheol-Hwee; Ahn, Jae-Pyong; Choi, Hyunjoo; Lee, Kon-Bae
Recently, we developed and reported an easy and cost-effective process called nitridation-induced self-forming Al composites (NISFAC) for manufacturing aluminum matrix composites from Al powder. In this process, AlN is formed by an in situ reaction between Al powder and nitrogen gas, and Al/AlN composites are self-sintered at temperatures below the melting point of aluminum because of the thermal energy released by the nitridation reaction of the Al powder. Because AlN is formed by an in situ reaction in the Al matrix, it is not only chemically stable, but also beneficial in terms of its wettability with the matrix. In this study, we prepared Al/AlN composites using the NISFAC process by increasing the amount of ex-situ added AlN reinforcement. The coefficient of thermal expansion (CTE) was effectively reduced by increasing the volume fraction of AlN, which was significantly lower than the theoretically expected value; a CTE of ∼10.8 × 10 −6 /°C could be achieved by adding only 20 vol.% of AlN. This demonstrates that the in situ formation of AlN during the NISFAC process may help reduce the CTE of Al/AlN composites.